Predictive model for recurrence of incisional hernia constructed by CT abdominal wall imaging features - Qi He; Yunhua Wu; Gexin Xu; Zhixing Zhang; Dejan Gao; Lingzhi Nie; Qingguo Du (BMC Surgery)
Abstract Background The recurrence rate after incisional hernia surgery is the most important concern for patients and surgeons, which not only causes pain to the patient but also adds additional medical costs. This study aims to investigate CT imaging features based on abdominal wall mechanics for recurrence after incisional hernia surgery. Materials and methods We collected data from patients who were diagnosed with incisional hernia and underwent hernia repair from January 2017 to January 2022 in Shanxi Provincial People's Hospital. Based on Laplace's equation, an equation for spherical wall pressure, we further measured the preoperative abdominal wall thickness and abdominal wall radius of the patients by CT and measured the abdominal wall muscle area and visceral fat area at the third lumbar level by using Slice-O-Matic 5.0 software, and the sarcopenia index was further obtained by dividing the muscle area by the square of the height. Then, we analyzed their relationship with the postoperative recurrence of incisional hernia. Results By univariate and multifactorial analyses, we found that excessive visceral adiposity, high BMI and sarcopenia were independent risk factors for incisional hernia recurrence. In further stratified analysis, we also found that patients with combined sarcopenia had a higher probability of recurrence. Our results found that visceral fat was a higher risk factor for incisional hernia recurrence than BMI. Conclusion This study was a retrospective study. Based on the Laplace equation, sarcopenia and visceral fat are independent risk factors for recurrence after incisional hernia.